Pengembangan Aplikasi Pelatihan Pendamping Pusat Studi dan Layanan Disabilitas Universitas Brawijaya (PSLD UB) Berbasis Android - Beni Dektos Heronimus; Fajar Pradana; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The Center for Study and Disability Services of Universitas Brawijaya, or commonly known as PSLD UB, is an institution at UB that has the function of providing assistance to students who have special needs. In the process of mentoring PSLD UB recruits students. the mentor will receive training on how to provide assistance to students with special needs in the learning process and academic activities within the university. Prospective assistants were given material and practice on the types of disabilities found in UB for two days such as sign language training. However, in practice, potential facilitators do not absorb the material well because the training time tends to be short. Because it is needed a mentoring training application system that has the function as a medium for further training for potential candidates in order to absorb the accompanying training material provided. Then obtained 23 functional needs and 1 non-functional needs and then implemented using the Java programming language with an Android-based platform using the SDLC method that is Waterfall which includes processes consisting of plans (planning), analysis (analysis), design (design), implementation (implementation), testing (testing) and maintenance (maintenance) as well as validation testing that produces a validation rate of 100% and usability testing is done based on the answers of respondents using a Likert scale so as to produce a value of 75.8 so that it falls into the acceptable category.